Use of systematic reviews in clinical practice guidelines: case study of smoking cessation. Issue 7317 (13th October 2001) - Silagy, C A; Stead, L F; Lancaster, T
Abstract: Objective: To examine the extent to which recommendations in the national guidelines for the cessation of smoking are based on evidence from systematic reviews of controlled trials. Design: Retrospective analysis of recommendations for the national guidelines for the cessation of smoking. Materials: National guidelines in clinical practice on smoking cessation published in English. Main outcome measures: The type of evidence (systematic review of controlled trials, individual trials, other studies, expert opinion) used to support each recommendation. We also assessed whether a Cochrane systematic review was available and could have been used in formulating the recommendation. Results: Four national smoking cessation guidelines (from Canada, New Zealand, the United Kingdom, and the United States) covering 105 recommendations were identified. An explicit evidence base for 100%, 89%, 68%, and 98% of recommendations, respectively, was detected, of which 60%, 56%, 59%, and 47% were based on systematic reviews of controlled studies. Cochrane systematic reviews could have been used to develop between 39% and 73% of recommendations but were actually used in 0% to 36% of recommendations. The UK guidelines had the highest proportion of recommendations based on Cochrane systematic reviews. Conclusions: Use of systematic reviews in guidelines is a measure of the "payback" on investment in research synthesis. Systematic reviews commonly underpinned recommendations in guidelines on smoking cessation. The extent to which they were used varied by country and there was evidence of duplication of effort in some areas. Greater international collaboration in developing and maintaining an evidence base of systematic reviews can improve the efficiency of use of research resources.